Complex Cascade Reaction Networks via Cross β Amyloid Nanotubes. Issue 1 (26th October 2020) - Chatterjee, Ayan; Mahato, Chiranjit; Das, Dibyendu
Abstract: Biocatalytic reaction networks integrate complex cascade transformations via spatial localization of multiple enzymes confined within the cellular milieu. Inspired by nature's ingenuity, we demonstrate that short peptide‐based cross‐β amyloid nanotubular hybrids can promote different kinds of cascade reactions, from simple two‐step, to multistep, to complex convergent cascades. The compartmentalizing ability of paracrystalline cross‐β phases was utilized to colocalize sarcosine oxidase (SOX) and hemin as an artificial peroxidase. Further, the catalytic potential of the amyloid nanotubes with ordered arrays of imidazoles were used as hydrolase mimic. The SOX‐hemin amyloid nanohybrids featuring a single extant enzyme could integrate different logic networks to access complex digital designs with the help of three concatenated AND gates and biologically relevant stimuli as inputs. Abstract : Amyloid‐based minimalistic systems are shown to demonstrate diverse cascade reaction networks, from simple two‐step, to multistep, to complex convergent cascades. Further, complex chemoelectronic computations were performed with the help of multi input, concatenated AND gates.